Aisheen. Still Alive in Gaza - Wadimoff, Nicolas (Switzerland : Al Jazeera Children's Channel ; AKKA Films Production, 2010)
A glimpse into the plight of those trying to get by in what director Nicolas Wadimoff has called “the world's largest prison.” Shot a few weeks after the end of Israel’s January 2009 offensive, the film captures the human suffering and devastation wrought on Gaza’s Palestinian residents as they struggle daily to survive.
Coproduction: Israel, Qatar, Switzerland. Verzio FF Submission
Duration: 01:24:00
Verzio Film Festival Submission
Keywords: Documentary films